Clinical evaluation of a novel fractional radiofrequency device for hair growth: Fractional radiofrequency for hair growth stimulation. Issue 3 (15th January 2018) - Verner, Ines; Lotti, Torello
Abstract: AGA is a common disorder. Different treatments are available to prevent hair loss and achieve hair growth with variable results. The purpose of the present study was to evaluate the efficacy and safety of a novel fractional radiofrequency (RF) device (HairLux, Innogen Technologies Ltd., Yokneam, Israel), to prevent hair loss and induce hair growth. Twenty‐five patients received 10 fractional RF treatments every 2 weeks, and were followed up 2 months after the last treatment. All patients were evaluated by global photography. In 10 patients, blinded manual hair counts were performed. Patients demonstrated less hair shedding, fuller hair, and faster hair growth. There was an average increase of 31.6% in hair density (based on hair counts) and 18% increase in hair shaft thickness. All subjects tolerated the treatments well. The HairLux device is effective and safe for hair growth stimulation in AGA. Ten treatment sessions are recommended to maximize results.